ORAL IDIOPATHIC HOMOGENEOUS LEUKOPLAKIA - Shamim, Thorakkal (Journal of Ayub Medical College Abbottabad, 2016)
Leukoplakia is referred as oral white lesions that cannot be clinically or pathologically characterized by any specific disease.1 Leukoplakia is the most common potentially malignant condition of the oral cavity clinically presented as homogeneous, speckled and verrucous types.2 This case report documents a case of idiopathic homogeneous leukoplakia involving floor of the mouth and ventral surface of the tongue in a 55 year old Indian woman with no apparent aetiology. This case also emphasis that the biopsy and histopathological examination are still considered to be the gold standard for the diagnosis of suspicious white lesion without any apparent aetiology. A 55-year-old Indian woman presented with white patch involving floor of the mouth and ventral surface of the tongue of size 4x5 cm for five months. (Figure-1).The patient had no history of smokeless tobacco use. The patient had burning sensation and pain on taking hot and spicy food. The lesion was soft in consistency with irregular surface. Regional lymphadenopathy was present. A provisional diagnosis of oral leukoplakia was made. A biopsy was performed and histopathology revealed parakeratinised stratified squamous epithelium with dysplastic changes in the epithelial cells such as basilar hyperplasia and hyperchromatism. Epithelium and connective tissue interface was intact. Connective tissue showed inflammatory cells (Figure-2). No recurrence was observed after a follow-up period of 4 years. This report describes a white patch involving floor of the mouth and ventral surface of the tongue that was diagnosed by histopathologic examination as moderate epithelial dysplasia and clinically as idiopathic homogeneous leukoplakia. Leukoplakia is the most common potentially malignant disorder of the oral cavity affecting the Indian population.3 According to its clinical presentation, oral leukoplakia can be categorised into homogeneous and non-homogeneous types. Homogeneous leukoplakia may be presented as uniformly white flat plaque with a smooth or relatively smooth surface and non-homogeneous leukoplakia may be presented as nodular or verrucous having a wrinkled or corrugated surface.4 The most common site for leukoplakia is the buccal mucosa followed by mandibular gingiva, tongue and the floor of the mouth.5Leukoplakia is showing malignant transformation rate from 1 to 17% with highest transformation rate for the lesions on the floor of the mouth, soft palate and tongue.6 The differential diagnoses for this case include candidiasis, lichen planus, frictional keratoses and lupus erythematosus.